The eruption time of the permanent dentition among Malate Catholic School children aged 5-15 years old - Prado, Melody Magdaliene A.
The knowledge on the time of eruption of permanent dentition greatly affects a dentist's plan of treatment. However, the currently available data have been based on other races, thus, giving dentists an insufficient reference for the Filipino setting. This study aims to determine the time of eruption of permanent dentition among Malate Catholic schoolchildren aged 5-15 years old of both male and female groups. An oral examination among the randomly selected subjects was conducted noting down each child's name, age , sex, date of birth as well as the presence of permanent teeth except the 3rd molars. The study has established the eruption time of the permanent dentition among Malate Catholic schoolchildren. It has also revealed that the female group showed an earlier eruption as compared to the male group and that the permanent teeth in the mandibular arch appeared earlier than their maxillary counterparts with the exception of 1st and 2nd premolars in males and la premolars alone in females.